2023
DOI: 10.3390/nu15153429
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Iron, Cobalamin, Folate, and Vitamin A Status among Stunted Children: A Cross-Sectional Study in Uganda

Abstract: Micronutrient deficiencies and stunting are prevalent. We assessed correlates of iron, cobalamin, folate, and vitamin A biomarkers in a cross-sectional study of stunted children aged 12–59 months in eastern Uganda. The biomarkers measured were serum ferritin (S-FE), soluble transferrin receptor (S-TfR), retinol binding protein (S-RBP), plasma cobalamin (P-Cob), methylmalonic acid (P-MMA), and folate (P-Fol). Using linear regression, we assessed socio-demography, stunting severity, malaria rapid test, and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…This has been demonstrated in studies (Caulfield et al, 1996 ; Grummer‐Strawn, 1993 ; Marquis et al, 1997 ) showing that still breastfed children were shorter and lighter than their nonbreastfed counterparts of the same age. This is in line with our findings including by (Mutumba et al, 2023 ), given that on top of poorer anthropometric indices, breastfed children had more anaemia and cobalamin deficient cases compared to the nonbreastfed, all suggesting that the poor development was not due to breastfeeding per se but rather the prolonged breastfeeding was being used as a countermeasure to other nutritional, clinical or physiological disruptions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This has been demonstrated in studies (Caulfield et al, 1996 ; Grummer‐Strawn, 1993 ; Marquis et al, 1997 ) showing that still breastfed children were shorter and lighter than their nonbreastfed counterparts of the same age. This is in line with our findings including by (Mutumba et al, 2023 ), given that on top of poorer anthropometric indices, breastfed children had more anaemia and cobalamin deficient cases compared to the nonbreastfed, all suggesting that the poor development was not due to breastfeeding per se but rather the prolonged breastfeeding was being used as a countermeasure to other nutritional, clinical or physiological disruptions.…”
Section: Discussionsupporting
confidence: 93%
“…Venous blood was drawn from each child, transported to the field laboratory, processed, and temporarily stored at −20°C before being transported to Kampala for storage at −80°C. Processed samples were later transferred to Denmark and Germany on dry ice for analysis of the micronutrient biomarkers and acute phase proteins as elaborated elsewhere including justification for cut‐offs (Mutumba et al, 2023 ). Before processing, whole blood was used to diagnose malaria (rapid diagnostic test RDT, SD bioline malaria Ag Pf, Abbott) and measure haemoglobin concentration (Hb201+, HemoCue).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that a large proportion of children with stunting had deficiencies of iron, vitamin A or cobalamin [14]. Iron is a key component of hem in red blood cells and iron deficiency is a prominent cause of childhood anemia [15].…”
Section: Introductionmentioning
confidence: 99%